84.8k views
3 votes
If f(x) = 3x + 2 and g(x) = 2x – 2, what is (f – g)(x)? A. x + 4 B. x – 2 C. x D. 5x – 2 E. x – 4

User Shovavnik
by
5.8k points

2 Answers

6 votes

Hello!

The answer is:

A.
x+4

Why?

To solve this problem we must remember the following property:


(f-g)(x)=f(x)-g(x)

Now, the given functions are:


f(x)=3x+2\\g(x)=2x-2

Then, calculating
(f-g)(x)


(f-g)(x)=f(x)-g(x)=(3x+2)-(2x-2)\\\\(f-g)(x)=(3x+2)-(2x-2)=3x+2-2x+2\\\\(f-g)(x)=3x+2-2x+2=x+4

So, the correct option is:

A.
x+4

Have a nice day!

User Jeff Wilhite
by
6.1k points
3 votes

Answer: Option A

Explanation:

Given the functions f(x) and g(x):


f(x) = 3x + 2


g(x)=2x-2


(f-g)(x)
indicates that you need to subtract the function
f(x) = 3x + 2 and the function
g(x)=2x-2.

Then:


(f-g)(x)=3x + 2-(2x-2)

Now, you need to dstribute the negative sign and then you have to add like terms. Then:


(f-g)(x)=3x + 2-2x+2\\\\(f-g)(x)=x+4

You can observe that this answer matches with the option A.

User Janusz Lenar
by
5.2k points